2016
DOI: 10.17275/per.15.36.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Rational Emotive Behavior Based on Academic Procrastination Prevention Training Programme of Effectiveness

Abstract: The research is an experimental study which has experimental and control groups, and based on pre-test, post-test, monitoring test model. Research group consists of second and third grade students of Primary School Education and Psychological Counseling undergraduate programmes in Giresun University Faculty of Educational Sciences. The research group was formed among the students whose academic procrastination tendency is middle or high, by using academic procrastination scale. 60 students, whose academic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
2
Order By: Relevance
“…Procrastinators procrastinate because, after assessing, they must reduce negative experiences or perceptions, such as stress-induced anxiety, through avoidance. The result examined the indirect effects of trait awe on procrastination via stress and found that individuals higher in trait awe experienced less stress, which, in turn, reduced individual procrastination, which is consistent with hypothesis and previous research ( Dümez and Barut, 2016 ; Dou et al, 2019 ; Bai et al, 2021 ). Short-Term Mood Regulation ( Sirois and Fuschia, 2014 ; STMR) suggests that procrastination is a failure of self-regulation due to individuals abandon future-valuable behaviors in order to avoid negative emotions ( Ackerman, 2005 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Procrastinators procrastinate because, after assessing, they must reduce negative experiences or perceptions, such as stress-induced anxiety, through avoidance. The result examined the indirect effects of trait awe on procrastination via stress and found that individuals higher in trait awe experienced less stress, which, in turn, reduced individual procrastination, which is consistent with hypothesis and previous research ( Dümez and Barut, 2016 ; Dou et al, 2019 ; Bai et al, 2021 ). Short-Term Mood Regulation ( Sirois and Fuschia, 2014 ; STMR) suggests that procrastination is a failure of self-regulation due to individuals abandon future-valuable behaviors in order to avoid negative emotions ( Ackerman, 2005 ).…”
Section: Discussionsupporting
confidence: 87%
“…Procrastination is an avoidance behavior ( Zhang et al, 2019a ) and its antecedent is the motivational trade-off between avoidance and approaching the task ( Zhang and Feng, 2017 ). According to empirical research, stress is significantly positively correlated with procrastination ( Stead et al, 2010 ) and has a positive effect on procrastination ( Dümez and Barut, 2016 ; Dou et al, 2019 ). Thus, we hypothesized that stress mediates the relationship between trait awe and procrastination.…”
Section: Introductionmentioning
confidence: 99%
“…O critério de exclusão foi: artigos de revisão. (Basso et al, 2013;Murta & Tróccoli, 2007), oito nos Estados Unidos (Adams, 2017;Bellman et al, 2015;Cleary & Horsfall, 2011;Glick & Orsillo, 2015;Green et al, 2011;Hillier et al, 2018;Kachgal et al, 2001;, três na Alemanha Hafner et al, 2016;Hafneret al, 2014), dois na Turquia (Daloglu & Vural, 2013;Düsmez & Barut, 2016), e apenas um na África do Sul (Makola, 2017), no Canadá (Bowering et al, 2017), na China (Wang et al, 2017), na Colômbia (Muñoz-Olano & Hurtado-Parrado, 2017, na Espanha (Arco-Tirado et al, 2011), na Finlândia (Auvinen et al, 2015), no Irã (Behnam et al, 2014). Não foi possível identificar as nacionalidades dos estudos de Berkenbosch, et al (2014), Daniel et al (2002), Davis e Abbitt (2013), Drozd et al (2013), Johnson et al (2016), Prevatt et al (2017), Rozental et al (2015), Scent e Boes (2014), Silfee et al (2016) e Van-Eerde (2003).…”
Section: Métodounclassified
“…Essa estratégia pode favorecer o desenvolvimento profissional e pessoal de ambos. No caso de sessões grupais, os resultados apontam para um melhor ajustamento pessoal e criação de vínculos afetivos.Apesar das singularidades inerentes às intervenções analisadas aqui, um ponto-chave desenvolvido e contemplado em diversas pesquisas é o estabelecimento de metas(Bellman et al, 2015;Daloglu & Vural, 2013;Düsmez & Barut, 2016;Hafner et al, 2016;Hillier et al, 2018;Muñoz-Olano & Hurtado-Parrado, 2017;Murta & Tróccoli, 2007;Prevatt et al, 2017;Rozental et al, 2015;Silfee et al, 2016;Wang et al, 2017).Essa habilidade refere-se à identificação de um propósito orientador para as suas ações. No caso de estudantes universitários que visam atingir um objetivo, como tirar uma nota x, o aluno deve organizar sua abordagem tendo consciência dos pequenos passos envolvidos para atingir o que desejaHafner et al, 2016;Muñoz-Olano & Hurtado-Parrado, 2017).…”
unclassified